209k views
15 votes
‼️⚠️⚠️‼️ HELP PLEASE WILL GIVE POINTS​

‼️⚠️⚠️‼️ HELP PLEASE WILL GIVE POINTS​-example-1
User SorryEh
by
5.6k points

1 Answer

8 votes

Answer:

m∠ABC=42°

Explanation:

m∠ABD=70°

⇒m∠ABD=m∠ABC+m∠CBD

⇒70°=(3x+33°)+(5x+13°)

70°=8x+46°

70°-46°=8x

24°=8x⇒x=3°

x=3°

Then,

m∠ABC=3x+33°

put x=3°, we get

m∠ABC=3×3°+33°=9°+33°

m∠ABC=42°

User Dominick
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.